1997
DOI: 10.1021/np9700376
|View full text |Cite
|
Sign up to set email alerts
|

Three Secoiridoid Glucosides Esterified with a Linear Monoterpene Unit and a Dimeric Secoiridoid Glucoside from Jasminum polyanthum

Abstract: Reinvestigation of the dried flowers of Jasminum polyanthum has led to the isolation of four new secoiridoid glucosides, namely, jaspofoliamosides A (1) and B (2), jaspolinaloside (3), and neopolyanoside (4). The structures of new compounds were elucidated on the basis of chemical and spectroscopic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Compounds (187) to (189) have 188 (Fig. (3)) [133,134,83]. Similar to (182), secoiridoid is connected to C-8 of the aglycone via ester linkage in both compounds (187) and (188).…”
Section: Teucrioside-3''''-o-methylether (40) and Teucrioside-3''''4mentioning
confidence: 83%
“…Compounds (187) to (189) have 188 (Fig. (3)) [133,134,83]. Similar to (182), secoiridoid is connected to C-8 of the aglycone via ester linkage in both compounds (187) and (188).…”
Section: Teucrioside-3''''-o-methylether (40) and Teucrioside-3''''4mentioning
confidence: 83%
“…10 The 1 H NMR spectrum of compound (1) ( [12][13][14][15] (gardenamide class), and some were obtained as metabolites produced by human 16 and rat intestinal bacteria. 17 Comparison with the published data of known iridoid alkaloids, such as (6) (Figure 1), and hemiacetal-secoiridoids 11,18 like (7) ( Figure 1) and compound (1) 11,18 showed that (1) it was neither a hemiacetal nor a nitrogen-containing iridoid (N-2) but that it was compatible with a C-1(N)O-2 substitution. This was also supported by the presence of the 1 H-1 H COSY correlation between H-1/NH, rather than the H-1/NH, H-3/NH correlations expected in the iridoid alkaloids, 17 and by UV and IR data indicating the presence of the chromophore -OOCC=CHO.…”
Section: Resultsmentioning
confidence: 86%